The effects of risks and environmental factors on bank cost efficiency: A study in East Asia and Pacific region - Thu Phan; Kevin James Daly; Anh Tuan Doan (Cogent Economics & Finance, 2018)
The interrelationship between risks and bank efficiency has received much attention in banking literature for years, especially after the Asian financial crisis in 1997 and the global financial crisis (GFC) in 2008. This study collected and analyzed the data of 247 banks of 12 developed and developing economies in East Asia and Pacific area over the 2003-2012 period to find the empirical evidence for that relationships. Using a stochastic frontier approach (SFA) to estimate bank cost efficiency, we found that there are significant relationships among risks, cost efficiency and environmental factors, but they are in different levels when comparing between developed and developing economies, or between the periods of pre- and post-2008 financial crisis.
Keywords: 330; bank efficiency; bank risks; bank performance; SFA; stochastic frontierapproach; Asian developed economies; Asian developing economies; efficiency and risksrelationship